1965
DOI: 10.1112/jlms/s1-40.1.260
|View full text |Cite
|
Sign up to set email alerts
|

On the Modulus of Power Series of a Certain Type

Abstract: In a recent publication B. Kuttner [4] has proven that the functions QO f K (z) which are defined for | z | < l by £ (n-\-l) K z n have the property n=0 f K (z) ^ 0 for | z | < 1, 1 < K < 2. It is the purpose of this paper to give a new proof of this result. We obtain it as a special case of a theorem on the modulus of power series where the coefficients are totally monotone. This theorem also yields a generahzation of Kakeya's theorem [3] under the same assumption about the coefficients.1. We remark that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In particular, if a + f (−1) ≥ 0, then we conclude that a + f (z) is non-vanishing on |z| < 1. If c = 0, this theorem reduces to the main result of [19].…”
Section: Resultsmentioning
confidence: 93%
“…In particular, if a + f (−1) ≥ 0, then we conclude that a + f (z) is non-vanishing on |z| < 1. If c = 0, this theorem reduces to the main result of [19].…”
Section: Resultsmentioning
confidence: 93%
“…In particular, if a + lim r→1 − f (−r) ≥ 0 and if f is non-constant, then we conclude that a + f (z) is non-vanishing on |z| < 1. If c = 0, this theorem reduces to the main result of [16].…”
Section: Resultsmentioning
confidence: 93%
“…is positive in -1 < x < 1 not only for the special functions y(t), but also for any arbitrary increasing function s(t) with s(l) < oo. For this purpose we replace y(t) by s(t) in / 1} where s(t) is independent of A-, and regard I y as a function of A-, say I t (x But /i(i)*H(i-0 2 (<+' 2 )**(0) M(i-t) 2…”
Section: -2xt + T 2 )Dy(t)jt(2t-x(\+t 2 ))Dy(t)mentioning
confidence: 99%
“…
In a recent paper A. Peyerimhoff [2] showed that if/(z) = tfo + Sn^itfn-i 2 " where a 0 is real and {q n } a totally monotonet sequence then | z | = r^ 1 implies that |/(z)| ^ f ( -r). [This result is only significant if a 0 ^ 0, since otherwise/(-r) < 0.]
…”
mentioning
confidence: 99%